Influence of vanadium on electrical and microstructural properties of CaCu3Ti4O12/CaTiO3 - Ramajo, L. (2010)
Microstructure, electrical properties and dielectric behavior of undoped and VO2-doped CaCu3Ti4O12/CaTiO3 (CCTO/CTO) systems, were investigated. Discs doped with 0-3 mol% of VO2 were sintered at 1075 degrees C CaTiO3 (CTO) was found as a secondary phase in every sample, but vanadium phases were not detected It was also observed that vanadium diminished the CCTO grain size and dramatically changed the microstructure. The dielectric constant decreased from 13,500 to 9800 epsilon(0) (at 2500 Hz) for undoped to V-doped-CCTO/CTO. Also, the breakdown voltage and the non-linear coefficient alpha increased from 500 to 5000 V/m and from 3 to 25, respectively. Energy dispersive X-ray results indicated that vanadium was incorporated in the composite structure. (C) 2010 Elsevier B V All rights reserved.